THE EFFECT OF ROLE PLAYING TECHNIQUE APPLIED ON STUDENTS` SPEAKING COMPETENCE - Budiana, Kartika Marta (Educate, 2013)
This study aims to see the effect of the role playing technique application in on students` speaking competence, that covers (1) How is the effect of Role Playing teaching technique applied to the students` speaking competence on experimental class; and (2) How is the effect of conventional teaching applied to students` speaking competence on control class. The study based on the several language teaching technique principles such as the role playing technique and the speaking itself and some related previous studies. This study uses quantitative approach, specifically the experimental one. In this technique, there are two groups as the subjects, experimental and control and two instruments. The experimental group contains thirty students and the control group contains twenty five students. The experimental group has the role playing technique as the treatment, while the control doesn`t. Before the treatment given, both of the group is given the pre-test to check their ability level. Then, after the treatment is given, the post-test is given to the both groups. The instruments to get the data are the oral test and questionnaire for the discussion. The subjects are the students of Junior High 2 level book program in YPIA English Course, Jalan Sumatera Branch, Surabaya. The data of this study is students` score and from the tests` score it can be seen there is a positive significant difference in the experimental group. The t-test to test hypothesize also shows that it is accepted which said that there is an improvement on the students` speaking competence achievement. In conclusion, the role playing application effects on the significant difference on the students speaking competence achievement. Keywords: Role Playing, Speaking Competence